Aqueous-phase reforming of xylitol over Pt/C and Pt/TiC-CDC catalysts: catalyst characterization and catalytic performance - Kirilin, Alexey V.; Hasse, Benjamin; Tokarev, Anton V.; Kustov, Leonid M.; Baeva, Galina N.; Bragina, Galina O.; Stakheev, Aleksandr Yu.; Rautio, Anne-Riikka; Salmi, Tapio; Etzold, Bastian; Mikkola, Jyri-Pekka; Murzin, Dmitry Yu. (Catalysis: Science and Technology, 2014)
The aqueous phase reforming (APR) of xylitol was studied over five Pt/C catalysts. The correlation between physico-chemical properties of the catalysts and catalytic performance was established. The Pt/C catalysts have different textural properties as well as different mean Pt cluster sizes and surface acidity. The average Pt cluster size was investigated by means of CO chemisorption as well as by TEM. The reaction was found to be structure sensitive and TOF linearly increases with increasing average Pt cluster size in the studied domain. The catalysts which possess higher surface acidity favoured higher rates of hydrocarbon production. On the contrary the Pt/C materials with lower acidities generated hydrogen with high selectivity and TOF.
EAM Import::2019-03-13

Preparation of carbide-derived carbon supported platinum catalysts - Hasse, Benjamin; Gläsel, Jan; Kern, Andreas; Murzin, D. Yu.; Etzold, Bastian (Catalysis Today, 2015)
Well defined carbon supported catalysts are of interest to deduce structure activity relationships and for catalyst optimization. Carbide-derived carbons (CDC) are high purity porous carbons with tunable pore structure. The deposition of platinum on silicon and titanium carbide based CDC was studied, using a three step process of acid treatment, ion-adsorption of platinum precursor and gas phase reduction. The influence of the steps on the carbon support properties and possibility to control the platinum loading and resulting cluster size was determined. Most crucial is the acid treatment step, where oxygen groups are introduced. At a too high degree of functionalization (non-carbon content above 30 wt%), which can result for nitric acid treatment, the pore structure is heavily attacked. For sulfuric acid treatments non-carbon contents below 15 wt% and only minor changes in the pore structure were observed. The ion-adsorption technique could be successfully transferred to the CDC supports. For medium to high degrees of functionalization (non-carbon contents above 20 wt%) the full deposition of 2.5 wt% of platinum was achieved. By the choice of platinum precursor, the pH of impregnation and the temperature of reduction the platinum cluster size could be varied from 2.5 to 5.3 nm. Thus, important knowledge how to prepare tuned Pt/C catalysts based on CDC and the ion-adsorption technique could be deduced.
EAM Import::2019-03-08

Titanium carbide-derived carbon as a novel support for platinum catalysts in direct methanol fuel cell application - Schlange, Alicja; Dos Santos, Antonio Rodolfo; Hasse, Benjamin; Etzold, Bastian; Kunz, Ulrich; Turek, Thomas (Journal of Power Sources, 2012)
The improvement of direct methanol fuel cells (DMFCs) requires the development of highly active catalysts. Carbide-derived carbon (CDC) is a new class of carbon materials which are produced via selective extraction of the non-carbon compounds from metal carbides. Nanoporous carbon with a surface area of 906 m2 g-1 and mean pore size of 3.4 nm was produced in consequence of chlorinating pure titanium carbide. This material was oxidatively treated to create the nucleation sites for the metal precursor. An increase of oxygen content in the carbon sample was observed after the functionalization step. The CDC material was subsequently loaded with 18.62 wt.% platinum, with an average particle size of 1.16 nm, by wet impregnation and chemical reduction. As a result, an enhanced electrochemical activity towards oxygen reduction was observed. The maximum power density of 50.16 mW cm-2 was achieved and is subsequently 18% higher than the value measured for commercial platinum catalyst (20 wt.% Pt) on activated carbon. This increase can be attributed to good catalyst dispersion, high surface area and small platinum cluster sizes, thus, confirming the potential of carbide-derived carbon supported catalysts for DMFC applications.
EAM Import::2019-03-13

Viscosity, Interfacial Tension, Density, and Refractive Index of Ionic Liquids [EMIM][MeSO3], [EMIM][MeOHPO2], [EMIM][OcSO(4)], and [BBIM][NTf2] in Dependence on Temperature at Atmospheric Pressure - Hasse, Benjamin; Lehmann, Julia; Assenbaum, Daniel; Wasserscheid, Peter; Leipertz, Alfred; Fröba, Andreas Paul (Journal of Chemical and Engineering Data, 2009)
This work represents a continuation of former investigations, where viscosity, interfacial tension, density, and refractive index of ionic liquids (ILs) [EMIM][EtSO4] (1-ethyl-3-methylimidazolium ethylsulfate), [EMIM][NTf2] (1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide), [EMIM][N(CN)(2)] (1-ethyl-3-methylimidazolium dicyanamide), and [OMA][NTf2)] (trioctylmethylammonium bis(trifluoromethylsulfonyl)imide) were studied. Here, the ILs [EMIM][MeSO3] (1-ethyl-3-methylimidazolium methanesulfonate), [EMIM][MeOHPO2] (1-ethyl-3-methylimidazolium methylphosphonate), [EMIM][OcSO(4)] (1-ethyl-3-methylimidazolium octylsulfate), and [BBIM][NTf2] (1-butyl-3-butylimidazolium bis(trifluoromethylsulfonyl)imide) were investigated again both by conventional techniques and by surface light scattering (SLS). An Abbe refractometer was used for the measurement of the refractive index in the range of (283.15 to 313.15) K with an expanded uncertainty (k = 2) of about 0.0005. The density was measured between (273.15 and 313.15) K with a vibrating tube densimeter and an expanded uncertainty (k = 2) of about 0.02%. The interfacial tension was obtained from the pendant drop technique at a temperature of 293.15 K with an expanded uncertainty (k = 2) of 1%. On the basis of this datum and the temperature dependence of density, the interfacial tension for all relevant temperatures was estimated via an appropriate prediction model. For the ILs studied within this work, at a first-order approximation, the quantity directly accessible by SLS was the ratio of dynamic viscosity to surface tension. Combining the results from SLS with values for density and interfacial tension from conventional methods, the dynamic viscosity could be obtained from (273.15 to 333.15) K with an estimated expanded uncertainty (k = 2) of less than 3%. Besides a comparison with the literature, the major aim of this work was to point out the influence of variations of the anion on thermophysical properties of [EMIM](+)-based ILs. In addition, the effect of different cations was studied in ILs with the [NTf2](-) anion. ILs with equal cations and similar anions can still exhibit different properties, which is interpreted with relevant molecular interactions.